2021
DOI: 10.1186/s12903-021-01513-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning based prediction of necessity for orthognathic surgery of skeletal malocclusion using cephalogram in Korean individuals

Abstract: Background Posteroanterior and lateral cephalogram have been widely used for evaluating the necessity of orthognathic surgery. The purpose of this study was to develop a deep learning network to automatically predict the need for orthodontic surgery using cephalogram. Methods The cephalograms of 840 patients (Class ll: 244, Class lll: 447, Facial asymmetry: 149) complaining about dentofacial dysmorphosis and/or a malocclusion were included. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 18 publications
(30 reference statements)
0
38
0
Order By: Relevance
“…Overall, the AI algorithm architecture (CNN, ANN) showed promising results in cephalometric landmark detection and analysis compared with human subjects, as shown in Table 1 . Moreover, 19 articles [ 5 , 6 , 8 , 9 , 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were excluded from this review, as shown in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the AI algorithm architecture (CNN, ANN) showed promising results in cephalometric landmark detection and analysis compared with human subjects, as shown in Table 1 . Moreover, 19 articles [ 5 , 6 , 8 , 9 , 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were excluded from this review, as shown in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…and 64.8%. 20 Similarly, Shin et al (2021) 21 and Lin et al (2021) 22 concluded, with an accuracy of 95.4% 21 and 87.4%, 22 respectively, that a deep learning program can be used to determine the need for orthognathic surgery. The latter publication also determined that it is possible to predict the future need for surgery to correct sagittal skeletal discrepancy in patients with repaired unilateral cleft lip and palate at the age of 6 years.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…Deep learning has developed rapidly in recent years, making it possible to automatically extract information in the medical field from diagnoses using medical imaging and pattern analysis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Deep neural networks (DNNs), a type of deep learning, have been widely applied to medical images because of their high performance in detection, classification, and segmentation [ 16 , 17 , 18 , 19 , 20 ]. It can reduce the labor of experts while detecting image information that may be missed by humans.…”
Section: Introductionmentioning
confidence: 99%